Travel photography. (New York : Time-Life Books, 1972)
The chapters in this book combine the advice of professionals with examples from their travels.
1. Have camera, will travel -- 2. The first pictures from afar -- 3. The well planned trip -- 4. The challenge of black and white -- 5. A sense of place -- 6. Such interesting people -- 7. Cliches revisited.
Includes bibliographical references and index.
Keywords: PHOTOGRAPHY